Could Phylogenetic Analysis Be Used for Feline Leukemia Virus (FeLV) Classification? - Lucía Cano-Ortiz; Caroline Tochetto; Paulo Michel Roehe; Ana Cláudia Franco; Dennis Maletich Junqueira (Viruses, 2022)
The surface envelope (SU) protein determines the cell tropism and consequently the pathogenesis of the feline leukemia virus (FeLV) in felids. Recombination of exogenous FeLV (exFeLV) with endogenous retroviruses (enFeLV) allows the emergence of more pathogenic variants. Currently, phenotypic testing through interference assays is the only method to distinguish among subgroups—namely, FeLV-A, -B, -C, -E, and -T. This study proposes a new method for FeLV classification based on molecular analysis of the SU gene. A total of 404 publicly available SU sequences were used to reconstruct a maximum likelihood tree. However, only 63 of these sequences had available information about phenotypic tests or subgroup assignments. Two major clusters were observed: (a) clade FeLV-A, which includes FeLV-A, FeLV-C, FeLV-E, and FeLV-T sequences, and (b) clade enFeLV, which includes FeLV-B and enFeLV strains. We found that FeLV-B, FeLV-C, FeLV-E, and FeLV-T SU sequences share similarities to FeLV-A viruses and most likely arose independently through mutation or recombination from this strain. FeLV-B and FeLV-C arose from recombination between FeLV-A and enFeLV viruses, whereas FeLV-T is a monophyletic subgroup that has probably originated from FeLV-A through combined events of deletions and insertions. Unfortunately, this study could not identify polymorphisms that are specifically linked to the FeLV-E subgroup. We propose that phylogenetic and recombination analysis together can explain the current phenotypic classification of FeLV viruses.